2012
DOI: 10.1016/j.epsl.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound on stylolite roughness as indicator for amount of dissolution

Abstract: Stylolites are rough surfaces formed by localized dissolution, mostly in carbonates and sandstones. They often account for a large degree of dissolution, and their impact on porosity and permeability is well recognized. Understanding their formation mechanism can advance our ability to predict their occurrence and effect on flow, which has appreciable geological and economical implications. Still, many fundamental issues concerning their structure and evolution are still unresolved. This manuscript studies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…It is a major mechanism in the pressure solution processes, which have been welldocumented in describing sedimentary and fault rock deformation (Durney, 1972;Rutter, 1983;Tada and Siever, 1989;Yasuhara et al, 2005), porosity-permeability evolution (Bjørkum and Nadeau, 1998;Ehrenberg et al, 2006), and development of stylolites in carbonate reservoir (Renard et al, 2004;Laronne Ben-Itzhak et al, 2012). One of the important implications of these processes is the formation of different pressure regimes in North Sea central graben, which impacts fluid pressure release and build-up (Swarbrick and Osborne, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is a major mechanism in the pressure solution processes, which have been welldocumented in describing sedimentary and fault rock deformation (Durney, 1972;Rutter, 1983;Tada and Siever, 1989;Yasuhara et al, 2005), porosity-permeability evolution (Bjørkum and Nadeau, 1998;Ehrenberg et al, 2006), and development of stylolites in carbonate reservoir (Renard et al, 2004;Laronne Ben-Itzhak et al, 2012). One of the important implications of these processes is the formation of different pressure regimes in North Sea central graben, which impacts fluid pressure release and build-up (Swarbrick and Osborne, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Not unexpectedly, the stylolites that develop during the earliest stages of dissolution are tiny (millimeter scale), but progressively the teeth may achieve centimeterscale amplitudes. Final average amplitude of stylolite teeth can be used as a guide only to the minimum magnitude of material loss (Ben-Itzhak et al, 2012). Simpson (1985) and Alvarez et al (1985) demonstrated that pressure dissolution produced by gravitational loading during burial and diagenesis commonly generates parallel, evenly spaced stylolite surfaces that resemble fl aggy bedding.…”
Section: Diagenetic Stylolitesmentioning
confidence: 99%
“…The stylolites differ in origin and morphology: from almost simple through wave-like to columnar and seismogram-like, according to the sequence of stylolite evolution (Fairbridge, 1968;Park & Schot, 1968;Strzetelski, 1977;Andrews & Railsbak, 1997;Sheppard, 2002;Sinha-Roy, 2002;Renard et al, 2004;Schmittbuhl et al, 2004;Brouste et al, 2007;Ben-Itzhak et al, 2012) (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Solutes are then transported to the zones of lower stress, in consistence with the Riecke principle (Füchtbauer, 1974). As a result, the stylolite seams can be filled with residue composed of e.g., clay minerals and/or organic matter (Park & Schot, 1968;Neugenbauer, 1973;Bathurst, 1975;Larsen & Chilingar, 1979;Choquette & James, 1990;Matyszkiewicz, 1996;Środoń, 1996;Agosta & Kirschner, 2003;Ehrenberg, 2006;Ben-Itzhak et al, 2012;Rustichelli et al, 2012).…”
Section: Compactionmentioning
confidence: 99%